A novel cecropin‐like peptide from black soldier fly, Hermetia illucens: Isolation, structural and functional characterization. Issue 2 (March 2017) - Park, Soon‐Ik; Yoe, Sung Moon
Abstract: Cecropins are basic antibacterial peptides that have potent antimicrobial activities. We induced and purified a novel antimicrobial peptide exhibiting activity against Gram‐negative bacteria from the immunized hemolymph of Hermetia illucens larvae . The immunized hemolymph was extracted, and the novel cecropin‐like peptide 1 (CLP1) was purified using solid‐phase extraction and reverse‐phase chromatography. The purified CLP1 demonstrated a molecular weight of 4, 840 Da, as determined by matrix‐assisted laser desorption/ionization‐time‐of‐flight (MALDI‐TOF). From analysis of CLP1 by N‐terminal amino acid sequencing using Edman degradation, combined with MALDI‐TOF and rapid amplification of cDNA ends‐polymerase chain reaction (RACE‐PCR), the amino acid sequence of the mature peptide was determined to be GWRKRVFKPVEKFGQRVRDAGVQGIAIAQQGANVLATARGGP PQQG. In NCBI BLAST, the amino acid sequence of CLP1 was found to be 60 % identical to the Drosophila melanogaster cecropin C. In silico analysis revealed that CLP1 was suggested to be part of the cecropin superfamily of AMPs characterized as cationic, linear, α‐helical, and amphipathic polypeptides. Analysis of the minimal inhibitory concentration (MIC) and the minimal bactericidal concentration (MBC) showed that CLP1 exerted antibacterial effects against Gram‐negative bacteria. The expression of CLP1 transcripts in several tissues after bacterial challenge was measured by quantitative real‐time PCR. CLP1 expression was negligible throughout the body before immunization, and was mostly evident in the fat body after immunization.